IMPROVED MATHEMATICS UNDERSTANDING OF TIME, DISTANCE AND SPEED USING TAMIYA GAME TOWARDS STUDENT WITH HEARING IMPAIRMENT - Rusyani, Endang; Sutisna, Nia; Hernawati, Ati; Maryanti, Rina; Husaeni, Dwi Fitria Al; Ragadhita, Risti (Jurnal Pengajaran MIPA, 2021)
This study aimed to determine the effect of using Tamiya's game in improving the mathematical understanding of students with hearing impairment on time, distance and speed. The method used was Classroom Action Research using Tamiya games as learning media. The research was conducted in two cycles using the Kemmis and Taggart model which consists of 4 components, namely planning, action, observation and reflection. From the research conducted, it was found that in cycle I, there was a slight increase in learning outcomes where 25% of students passed and 75% did not graduate from the initial conditions, 100% of students passed the class with an average score of 53.75. In cycle II there was a significant change, 100% of students passed after making learning improvements from cycle I, an active learning situation emerged and an increase in learning outcomes. These results were obtained due to an increase in the involvement of teachers and students in learning. The use of Tamiya games as a concrete learning medium by involving students in direct experience could help the limitations of deaf children in receiving information and abstraction power that cause obstacles to knowledge achievement. The impact of this study shows that the use of the Tamiya game as a concrete learning medium could improve the mathematical understanding of the topic of time, distance and speed towards fifth grade students with hearing impairment.